2017
DOI: 10.1126/science.aam6203
|View full text |Cite
|
Sign up to set email alerts
|

Metalloprotein entatic control of ligand-metal bonds quantified by ultrafast x-ray spectroscopy

Abstract: The multifunctional protein cytochrome c (cyt c) plays key roles in electron transport and apoptosis, switching function by modulating bonding between a heme iron and the sulfur in a methionine residue. This Fe–S(Met) bond is too weak to persist in the absence of protein constraints. We ruptured the bond in ferrous cyt c using an optical laser pulse and monitored the bond reformation within the protein active site using ultrafast x-ray pulses from an x-ray free-electron laser, determining that the Fe–S(Met) bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
140
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(154 citation statements)
references
References 43 publications
(58 reference statements)
8
140
1
1
Order By: Relevance
“…Addressing the discrepancies between the interpretation of ultrafast optical spectroscopy and quantum dynamics studies requires robust signatures for MLCT and MC excited states and motivates our time-resolved XES and WAXS study of the coupled electronic and structural dynamics of [Fe(bmip)2] 2+ . Contrary to prior ultrafast XES measurements on transition metal complexes [10][11][12][13][14], the Kα XES signal of [Fe(bmip)2] 2+ shows the signature of vibrational wavepacket dynamics. We verify the assignment of the oscillations in the Ka XES signal with the simultaneous observation of the same wavepacket dynamics with WAXS and assign the oscillations to a Fe-ligand bond stretching coordinate of a 3 MC excited state.…”
Section: Introductioncontrasting
confidence: 76%
See 2 more Smart Citations
“…Addressing the discrepancies between the interpretation of ultrafast optical spectroscopy and quantum dynamics studies requires robust signatures for MLCT and MC excited states and motivates our time-resolved XES and WAXS study of the coupled electronic and structural dynamics of [Fe(bmip)2] 2+ . Contrary to prior ultrafast XES measurements on transition metal complexes [10][11][12][13][14], the Kα XES signal of [Fe(bmip)2] 2+ shows the signature of vibrational wavepacket dynamics. We verify the assignment of the oscillations in the Ka XES signal with the simultaneous observation of the same wavepacket dynamics with WAXS and assign the oscillations to a Fe-ligand bond stretching coordinate of a 3 MC excited state.…”
Section: Introductioncontrasting
confidence: 76%
“…A powerful method to disentangle the electronic and nuclear motions of 3d transition metal complexes during ultrafast nonadiabatic processes is time-resolved 1s-2p (Ka) and 1s-3p (Kβ) X-ray Emission Spectroscopy (XES) [10][11][12][13][14] combined with Wide Angle X-ray Scattering (WAXS) [15][16][17][18][19][20][21][22][23]. These experiments have been utilized to assign the electronic and structural motions during excited state dynamics [24][25][26] and to project the locations of conical intersections between excited state potential energy surfaces onto critical structural coordinates [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, following the fs Fe K-edge XAS experiment on Carboxymyoglobin (MbCO) at single probe energies, 132 polarized fs Co K-edge XANES on Vitamin B12 was for the first time reported, probing the structural evolution of the protein 141 . In another study, Mara and co-workers reported an ultrafast energy-resolved XAS and XES study of photoexcited ferrous Cytochrome C 142 . These various studies illustrate the diversity of systems one can investigate by fs X-ray spectroscopy at XFELs.…”
Section: Applications In Chemistrymentioning
confidence: 99%
“…The M100D mutation also substantially improved carbene transfer reactivity for Si–H insertion catalyzed by Rma cyt c 6 . This improvement in catalytic performance is likely due to removal of the axial ligand from the haem iron, which opens a site primed for iron carbenoid formation and subsequent product formation 32 . Two subsequent rounds of mutagenesis and screening led to variant BOR R1 (V75R M100D M103T), which exhibited a turnover of 2490 and an e.r.…”
mentioning
confidence: 99%